2021
DOI: 10.21037/tlcr-20-920
|View full text |Cite
|
Sign up to set email alerts
|

Role of the epithelial-mesenchymal transition-related circular RNA, circ-10720, in non-small-cell lung cancer

Abstract: Background: Circular RNAs (circRNAs) are non-coding RNAs with a circular structure that have recently emerged as important regulators of tumorogenesis. Recently, several circRNAS, including circ-10720 have been related to epithelial-mesenchymal transition (EMT) process. In the present study, we have analyzed the role of circ-10720 in non-small-cell lung cancer (NSCLC) and studied its prognostic relevance in resected stage I-IIIa NSCLC patients.Methods: Circ-10720 expression was analyzed using a custom TaqMan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Plasmid transfection was performed according to the instructions. The transfection reagent used is lipofectamine 2000 (Invitrogen) [26].…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
“…Plasmid transfection was performed according to the instructions. The transfection reagent used is lipofectamine 2000 (Invitrogen) [26].…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
“…The regulatory role of hsa_circ_0018189 in NSCLC has been confirmed, but its specific mechanism has not been reported, 16 so we did further exploratory experiments. Starbase prediction revealed that miR‐656‐3p might interact with hsa_circ_0018189.…”
Section: Discussionmentioning
confidence: 99%
“… 12 More and more studies on circRNAs in NSCLC have proved the action of circRNAs in the occurrence and development of NSCLC. 13 , 14 , 15 Hsa_circ_0018189 was suggested to exert a significant function in NSCLC, 16 but its specific functional mechanism has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, circIGF2BP3 facilitates carcinoma cell immune evasion in NSCLC 8 . CircCUL2 plays a promoting effect on NSCLC cell epithelial‐mesenchymal transition (EMT) 9 . Hsa_circ_0001492, also known as circERBB2IP, is derived from the ERBB2IP gene.…”
Section: Introductionmentioning
confidence: 99%